An interesting case of back pain - Rai, Pratheeksha G.; Subramanya, Chethan (International Journal of Research in Medical Sciences, 2018)
Meliodosis is a disease caused by gram negative bacterium Burkholderia pseudomallei. Among its various clinical presentations, involvement of spine is rare phenomenon. On presentation they mimic tuberculosis and malignancy. We present a case of an elderly male with known case of diabetes mellitus presented with fever of unknown origin associated with back pain. On evaluation, all tests for tuberculosis and malignancy remained negative. Multiple visceral abscesses with hyper intense foci in T4vertebrae were seen. Pleural fluid culture grew Burkholderia pseudomallei. Patient was treated with parenteral meropenem for 2 weeks, oral doxycycline and trimethoprim/sulphamethazone for 12 weeks. Dramatic decrease in back pain with improvement of constitutional symptoms was seen within 2 days of initiation of appropriate antibiotics. Meliodosis should be considered in differential diagnosis of back pain with constitutional symptoms. Dedicated team of microbiologists and physicians is required to identify and treat the disease.